Plugged and Unplugged Coding Approaches for Developing Computational Thinking in Early Childhood: A Systematic Literature Review - Anita Damayanti; Ajeng Afkarina Irvana Bella; Imelda Indah Lestari; Dewi Mayangsari (Nak-Kanak: Journal of Child Research, 2026)
Background of the study: The integration of coding activities in early childhood education has gained increasing attention as computational thinking (CT) is recognized as an essential twenty-first-century skill. Previous studies have explored both plugged and unplugged coding approaches for young children; however, limited research has systematically synthesized and compared the empirical evidence regarding their effectiveness in developing computational thinking among children aged 4–6 years, particularly within the context of developing countries and resource-limited early childhood education settings. Aims and scope of paper: This study aimed to identify patterns, contradictions, and the strength of empirical evidence related to plugged and unplugged coding approaches in fostering computational thinking skills among early childhood learners through a systematic literature review. Methods: This study employed a systematic literature review design guided by the PRISMA 2020 framework. A total of 30 scholarly articles published between 2020 and 2025 and indexed in Scopus and SINTA were selected through predefined inclusion and exclusion criteria. The selected studies were analyzed using critical thematic synthesis to examine trends, learning outcomes, pedagogical characteristics, and contextual implementation of plugged and unplugged coding approaches in early childhood education. Results: The findings revealed that unplugged coding approaches consistently supported the development of foundational algorithmic understanding, problem decomposition, collaboration, and social interaction among young children. In contrast, plugged coding approaches demonstrated stronger contributions to abstraction visualization, sequential reasoning, and cognitive flexibility through interactive digital environments. The review found no absolute superiority between the two approaches, as both provided complementary contributions to computational thinking development. Furthermore, contextual factors such as teacher readiness, technological infrastructure, children’s developmental stages, and institutional resources significantly influenced the effectiveness of implementation. Contribution: The framework combines Piagetian cognitive development principles, Vygotskian scaffolding perspectives, and contextual resource considerations relevant to early childhood institutions in developing countries, particularly Indonesia.